A crack-resistant and seepage-proof concrete cement pole and a preparation method thereof

By using reinforcing materials such as multi-substance modified basalt fiber and carbon fiber in concrete cement poles, the problems of insufficient anti-cracking and anti-permeability performance in the existing technology are solved, a balance between compressive strength and anti-permeability performance is achieved, and the Material durability and compactness.

CN118993659BActive Publication Date: 2025-01-24BAOTOU MENGLU POWER EQUIP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411493616.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Existing concrete cement poles have shortcomings in cracking and permeability resistance, and in the process of improving permeability, it often leads to a decrease in compressive strength, making it difficult to find a balance between the two.

Method used

Reinforcing materials such as multi-substance modified basalt fiber and carbon fiber are used to improve the roughness and stability of the fiber surface through alkali etching and graft modification, and are coupled with the fiber through a silane coupling agent to form a reinforced concrete structure. Improve compressive strength and impermeability properties.

Benefits of technology

It achieves a balance between the compressive strength and impermeability properties of concrete cement poles, improves the durability and compactness of the material, and enhances its stability in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993659B_ABST
    Figure CN118993659B_ABST
Patent Text Reader

Abstract

The invention discloses a crack-resistant and anti-seepage concrete cement pole and a preparation method thereof, belonging to the technical field of concrete cement poles. The concrete of the concrete cement pole comprises, by weight, 300-350 parts of silicate cement, 100-120 parts of fine sand, 40-60 parts of fly ash, 100-150 parts of slag powder, 150-200 parts of coarse aggregate, 100-150 parts of water, 30-50 parts of multi-substance modified basalt fiber, 10-40 parts of carbon fiber, 10-40 parts of polypropylene fiber and 5-8 parts of water reducer. The present invention performs alkali treatment on basalt fiber to make its surface rough, which is conducive to the adsorption of trisodium 1,6-diphosphate fructose and graphene oxide, improves the durability and crack resistance of concrete, enhances the interface bonding strength and material compactness, and improves the compression resistance and impermeability. 4-Sulfonic acid calixarene is combined with 6,6'-iminodi-1-hexanol and then coupled to basalt fiber. The structure of calixarene gives stability to basalt fiber, improves structural strength, reduces water penetration channels, reduces fiber agglomeration, enhances bonding strength with concrete, and provides anti-cracking and anti-seepage properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete cement poles, and in particular relates to a crack-resistant and seepage-proof concrete cement pole and a preparation method thereof. Background Art

[0002] Concrete cement poles occupy a vital position in modern power, communication and other engineering fields. As key facilities supporting wires, cables and other equipment, their quality and performance directly affect the stable operation of the entire engineering system. Electric poles are usually made of reinforced concrete. With their remarkable characteristics such as high strength and good durability, they can stand firm in various complex natural environments. Whether it is the raging wind, the scouring of heavy rain, the exposure of the scorching sun, the invasion of severe cold, or even the freeze-thaw cycle brought by the alternation of seasons, electric poles need to withstand these severe tests. As the main component of electric poles, the quality of electric poles is directly determined by the performance of concrete. However, the existing ordinary concrete materials have many shortcomings. On the one hand, ordinary concrete has natural defects such as pores and fine cracks in its microstructure. These pores and fine cracks are like tiny channels, which greatly reduce the airtightness of concrete. Under the penetration of external moisture, these channels will gradually expand, resulting in poor anti-permeability of concrete. On the other hand, the tensile strength of ordinary concrete is relatively low, which makes it easy to crack when subjected to external stress. Once cracks appear in concrete, water can more easily penetrate into it, further reducing the concrete's impermeability.

[0003] At present, in order to improve the impermeability of concrete, engineering and technical personnel usually adopt the method of adding additives such as expansion agents to concrete materials. However, this method is not perfect. If too many expansion agents and other ingredients are added, although the impermeability of concrete can be improved to a certain extent, it will also cause other important properties of concrete, such as compressive strength, to decline. This is extremely unfavorable for concrete cement poles, because during use, poles not only need to have good impermeability, but also must have sufficiently high compressive strength to ensure that they can withstand the weight of equipment such as wires and cables and various pressures brought by the external natural environment. Under the working environment requirements of concrete cement poles, the concrete part urgently needs to have good crack resistance and impermeability at the same time. How to make concrete have both excellent strength and excellent crack resistance and impermeability without reducing key properties such as concrete compressive strength has become a difficult problem that needs to be solved urgently. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides an impermeable concrete with good performance, durability, high compressive strength and good impermeability, which solves the problem of poor durability and impermeability of current concrete cement poles.

[0005] In order to achieve the above-mentioned purpose, the following technical scheme is adopted: on the one hand, the present invention provides a crack-resistant and anti-seepage concrete cement pole, which is composed of concrete and a steel skeleton buried in the concrete; the concrete comprises the following components by weight: 300-350 parts of silicate cement, 100-120 parts of fine sand, 40-60 parts of fly ash, 100-150 parts of slag powder, 150-200 parts of coarse aggregate, 100-150 parts of water, 30-50 parts of multi-substance modified basalt fiber, 10-40 parts of carbon fiber, 10-40 parts of polypropylene fiber and 5-8 parts of water reducer.

[0006] Furthermore, the multi-substance modified basalt fiber is prepared by the following steps:

[0007] S1, dissolving 6,6'-iminodi-1-hexanol in dimethyl sulfoxide, then adding 4-sulfonic acid calixarene, heating to 70°C for reaction for 1.5h, then adding 4 mol / L sodium hydroxide solution to adjust the reaction solution to neutral, filtering, separating the liquids, and removing the solvent from the organic phase under reduced pressure to obtain grafted modified 4-sulfonic acid calixarene;

[0008] S2, immersing the basalt fiber in a 4 mol / L sodium hydroxide solution, stirring at 100°C for 2 h, then filtering, washing and drying to obtain an alkali-etched basalt fiber, dispersing trisodium 1,6-diphosphate fructose and graphene oxide in ethanol, then adding the alkali-etched basalt fiber, soaking for 10 min for adsorption assembly, then taking out and drying to obtain a basalt fiber coated with the composite;

[0009] S3, adding the composite-coated basalt fiber, grafted modified 4-sulfonic acid calixarene and silane coupling agent into deionized water, stirring at 80° C. for 3 h, then taking out and drying to obtain the multi-substance modified basalt fiber.

[0010] Furthermore, in step S1, the weight ratio of 6,6'-iminodi-1-hexanol, dimethyl sulfoxide and 4-sulfonic acid calixarene is 1:55-75:0.3-0.5.

[0011] Furthermore, in step S2, the weight ratio of trisodium fructose-1,6-diphosphate, graphene oxide, ethanol and alkali-etched basalt fiber is 3:2-5:300-500:10-20.

[0012] Furthermore, in step S3, the weight ratio of basalt fiber, grafted modified 4-sulfonic acid calixarene, silane coupling agent and deionized water is 10:1-3:0.5-1:300-500.

[0013] Furthermore, the silane coupling agent is one of KH550, KH560, KH570, KH602 and KH792, and the silane coupling agent is preferably KH792.

[0014] Furthermore, the fine sand is river sand with a fineness modulus of 2.3-3.0 and a bulk density of 1500-1800 kg / m3.

[0015] Furthermore, the fly ash is S105 steel slag, with a particle size of less than 3 mm and a bulk density of 2500-3000 kg / m3.

[0016] Furthermore, the particle size of the coarse aggregate is 5-10 mm.

[0017] Furthermore, the water reducer is a combination of one or more of sodium lignin sulfonate, sodium gluconate, melamine and polycarboxylic acid water reducer, and the water reducer is preferably a combination of sodium lignin sulfonate, melamine and polycarboxylic acid water reducer.

[0018] On the other hand, the present invention also provides a method for preparing a crack-resistant and anti-seepage concrete cement pole, comprising the following steps:

[0019] (1) After fine sand, coarse aggregate, multi-material modified basalt fiber, carbon fiber, and polypropylene fiber are mixed, silicate cement, fly ash, and slag powder are added for further mixing, and finally a water reducer and water are added to form concrete;

[0020] (2) pouring concrete into a mold equipped with a steel mesh, centrifugally forming, curing for 18 hours, and obtaining the concrete cement pole after demoulding.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention performs alkali treatment on basalt fiber to increase the surface roughness of the basalt fiber. The rough surface can better adsorb and assemble 1,6-diphosphate trisodium fructose and graphene oxide. The presence of 1,6-diphosphate trisodium fructose and graphene oxide effectively improves the durability of concrete. The wrinkled morphology of graphene oxide can form a mechanical interlock with the rough surface of the basalt fiber after alkali treatment, which not only enhances the overall stability of the material, but also provides the concrete with stronger crack resistance. The polar groups of 1,6-diphosphate trisodium fructose promote the bonding of the carboxyl and hydroxyl groups on the graphene oxide with the surface of the basalt fiber. , further enhancing the hydrophilicity and wettability of the basalt fiber surface, improving the dispersibility of basalt fiber in concrete mortar, and graphene oxide can also overlap and bridge with cement to form a criss-cross network structure, so that the interfacial bonding strength between basalt fiber and cement-based matrix is ​​significantly improved, which not only improves the interface performance between basalt fiber and concrete, but also improves the bonding force between concrete materials. Therefore, through the modification of basalt fiber by the two, the compactness of concrete materials is improved, and the compression resistance and impermeability of concrete are improved, which provides guarantee for the long-term and stable use of concrete cement poles in various complex environments;

[0023] (2) The present invention combines 4-sulfonic acid calixarene with 6,6'-iminodi-1-hexanol, and then couples the grafted modified 4-sulfonic acid calixarene with basalt fiber through a silane coupling agent. 4-sulfonic acid calixarene has a unique cup-like ring structure, which gives it a certain steric hindrance and rigidity, making the basalt fiber have high stability and improving the structural strength of concrete cement poles. Calixarene has a strong complexing ability. Through the extension of basalt fiber in various places in concrete, calixarene can combine with metal ions to produce substances that can block the pores of concrete. These substances reduce the penetration channels of water, greatly The anti-seepage performance of concrete is improved significantly. After the cup-shaped aromatic hydrocarbon forms a stable bond with the surface of basalt fiber, the agglomeration phenomenon between fibers is further reduced, and the dispersion of basalt fiber in the concrete matrix is ​​improved. 6,6'-Iminodi-1-hexanol is connected to the ring structure of cup-shaped aromatic hydrocarbon. Its chain segments can extend into the concrete from two directions, and the terminal hydroxyl groups enhance the bonding strength between basalt fiber and concrete matrix. Therefore, it can effectively fill the pores and cracks in concrete, further reducing the water penetration channel. Through the above mechanism of action, it provides excellent anti-cracking and anti-seepage performance for concrete cement poles. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The microscopic morphology observation results of multi-substance modified basalt fiber in Example 3 of the present invention;

[0025] Figure 2The concrete strength test results of Examples 1-3 and Comparative Examples 1-4 of the present invention are as follows;

[0026] Figure 3 The concrete shrinkage performance test results of Examples 1-3 and Comparative Examples 1-4 of the present invention are as follows;

[0027] Figure 4 These are the test results of the concrete impermeability of Examples 1-3 of the present invention and Comparative Examples 1-4.

[0028] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0031] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0032] In various embodiments and comparative examples of the present invention:

[0033] The multi-substance modified basalt fiber is prepared by the following steps:

[0034] S1, dissolving 6,6'-iminodi-1-hexanol in dimethyl sulfoxide, then adding 4-sulfonic acid calixarene, heating to 70°C for reaction for 1.5h, then adding 4 mol / L sodium hydroxide solution to adjust the reaction solution to neutral, filtering, separating the liquids, and removing the solvent from the organic phase under reduced pressure to obtain grafted modified 4-sulfonic acid calixarene;

[0035] S2, immersing the basalt fiber in a 4 mol / L sodium hydroxide solution, stirring at 100°C for 2 h, then filtering, washing and drying to obtain an alkali-etched basalt fiber, dispersing trisodium 1,6-diphosphate fructose and graphene oxide in ethanol, then adding the alkali-etched basalt fiber, soaking for 10 min for adsorption assembly, then taking out and drying to obtain a basalt fiber coated with the composite;

[0036] S3, adding the composite-coated basalt fiber, grafted modified 4-sulfonic acid calixarene and silane coupling agent into deionized water, stirring at 80° C. for 3 h, then taking out and drying to obtain the multi-substance modified basalt fiber.

[0037] The fine sand is river sand, with a fineness modulus of 2.3-3.0 and a bulk density of 1500-1800kg / m3;

[0038] The fly ash is S105 steel slag, with a particle size of less than 3mm and a bulk density of 2500-3000kg / m3;

[0039] The particle size of the coarse aggregate is 5-10 mm. Example 1

[0040] A crack-resistant and seepage-proof concrete cement pole

[0041] The concrete cement pole is composed of concrete and a steel skeleton buried in the concrete; the concrete includes the following components by weight: 300 parts of silicate cement, 100 parts of fine sand, 40 parts of fly ash, 100 parts of slag powder, 150 parts of coarse aggregate, 100 parts of water, 30 parts of multi-substance modified basalt fiber, 10 parts of carbon fiber, 10 parts of polypropylene fiber and 5 parts of water reducer.

[0042] In the step S1, the weight ratio of 6,6'-iminodi-1-hexanol, dimethyl sulfoxide and 4-sulfonic acid calixarene is 1:55:0.3; in the step S2, the weight ratio of trisodium salt of 1,6-diphosphate fructose, graphene oxide, ethanol and alkali-etched basalt fiber is 3:2:300:10; in the step S3, the weight ratio of basalt fiber, grafted modified 4-sulfonic acid calixarene, silane coupling agent and deionized water is 10:1:0.5:300; the silane coupling agent is KH550; and the water reducer is sodium lignin sulfonate. Example 2

[0043] A crack-resistant and seepage-proof concrete cement pole

[0044] The concrete cement pole is composed of concrete and a steel skeleton buried in the concrete; the concrete includes the following components by weight: 350 parts of silicate cement, 120 parts of fine sand, 60 parts of fly ash, 150 parts of slag powder, 200 parts of coarse aggregate, 150 parts of water, 50 parts of multi-substance modified basalt fiber, 40 parts of carbon fiber, 40 parts of polypropylene fiber and 8 parts of water reducer.

[0045] In the step S1, the weight ratio of 6,6'-iminodi-1-hexanol, dimethyl sulfoxide and 4-sulfonic acid calixarene is 1:75:0.5; in the step S2, the weight ratio of 1,6-diphosphate fructose trisodium salt, graphene oxide, ethanol and alkali-etched basalt fiber is 3:5:500:20; in the step S3, the weight ratio of basalt fiber, grafted modified 4-sulfonic acid calixarene, silane coupling agent and deionized water is 10:3:1:500; the silane coupling agent is KH560; and the water reducer is melamine. Example 3

[0046] A crack-resistant and seepage-proof concrete cement pole

[0047] The concrete cement pole is composed of concrete and a steel skeleton buried in the concrete; the concrete includes the following components by weight: 335 parts of silicate cement, 118 parts of fine sand, 45 parts of fly ash, 120 parts of slag powder, 170 parts of coarse aggregate, 115 parts of water, 36 parts of multi-substance modified basalt fiber, 15 parts of carbon fiber, 28 parts of polypropylene fiber and 6 parts of water reducer.

[0048] In the step S1, the weight ratio of 6,6'-iminodi-1-hexanol, dimethyl sulfoxide and 4-sulfonic acid calixarene is 1:60:0.4; in the step S2, the weight ratio of trisodium 1,6-diphosphate fructose, graphene oxide, ethanol and alkali-etched basalt fiber is 3:3:400:15; in the step S3, the weight ratio of basalt fiber, grafted modified 4-sulfonic acid calixarene, silane coupling agent and deionized water is 10:2.5:0.8:425; the silane coupling agent is KH792; the water reducer is a combination of sodium lignin sulfonate, melamine and polycarboxylic acid water reducer in a mass ratio of 2:2:3. Example 4

[0049] Preparation method of crack-resistant and seepage-proof concrete cement pole

[0050] The following steps are involved:

[0051] (1) After fine sand, coarse aggregate, multi-material modified basalt fiber, carbon fiber, and polypropylene fiber are mixed, silicate cement, fly ash, and slag powder are added for further mixing, and finally a water reducer and water are added to form concrete;

[0052] (2) pouring concrete into a mold equipped with a steel mesh, centrifugally forming, curing for 18 hours, and obtaining the concrete cement pole after demoulding.

[0053] Comparative Example 1

[0054] The difference between this comparative example and Example 3 is that unmodified basalt fiber is used instead of multi-substance modified basalt fiber, and the rest is the same as Example 3.

[0055] Comparative Example 2

[0056] The difference between this comparative example and Example 3 is that ungrafted modified 4-sulfonic acid calixarene is used instead of grafted modified 4-sulfonic acid calixarene, and the rest is the same as Example 3.

[0057] Comparative Example 3

[0058] The difference between this comparative example and Example 3 is that the components do not include trisodium fructose 1,6-diphosphate, and the rest are the same as Example 3.

[0059] Comparative Example 4

[0060] The difference between this comparative example and Example 3 is that graphene oxide is not included in the components, and the rest is the same as Example 3.

[0061] Test Example 1

[0062] Observation of microstructure of basalt fiber after modification

[0063] The microscopic morphology of the multi-substance modified basalt fiber in Example 3 was observed using a FEI Inspect scanning electron microscope. Figure 1 .

[0064] pass Figure 1 It can be seen that the modified basalt fiber in Example 3 of the present invention is grafted with 4-sulfonic acid calixarene to allow 1,6-diphosphate fructose trisodium salt and graphene oxide to be better adsorbed and assembled on the surface of the basalt fiber. The stacking degree of the fiber surface is high and regular. This structural transformation helps to improve the dispersion of basalt fiber in concrete. Graphene oxide can overlap and bridge with cement to form a criss-cross network structure, so that the basalt fiber can better combine with the cement slurry in the concrete, thereby improving the compactness of the concrete, thereby enhancing the durability of the concrete and improving the mechanical properties of the concrete.

[0065] Test Example 2

[0066] Concrete strength test

[0067] According to GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the concrete prepared in each embodiment and comparative example was tested for flexural strength and compressive strength. The results are shown in Figure 2 .

[0068] Depend on Figure 2 It can be seen that the concretes of Examples 1-3 all have high flexural strength and compressive strength. This is because after the basalt fiber is modified with multiple substances in the examples, the surface roughness of the basalt fiber after alkali treatment increases, which can better adsorb and assemble 1,6-diphosphate trisodium fructose and graphene oxide. The wrinkled morphology of graphene oxide forms a mechanical interlock with the rough surface of the basalt fiber, which enhances the overall stability and crack resistance of the material. At the same time, the polar groups of 1,6-diphosphate trisodium fructose promote the bonding of the carboxyl and hydroxyl groups on the graphene oxide to the surface of the basalt fiber, thereby improving the hydrophilicity and wettability of the basalt fiber surface. The dispersion of 4-sulfonic acid calixarene in concrete mortar is better, and the two work together to improve the density of concrete materials, thereby improving the compressive resistance of concrete. After 4-sulfonic acid calixarene is combined with 6,6'-iminodi-1-hexanol, it is coupled with basalt fiber through a silane coupling agent. The unique ring structure of 4-sulfonic acid calixarene gives basalt fiber higher stability, thereby improving the structural strength of concrete cement poles. The chain segments of 6,6'-iminodi-1-hexanol can extend into the concrete from two directions and enhance the bonding strength between basalt fiber and concrete matrix through terminal hydroxyl groups, further improving the strength of concrete.

[0069] Test Example 3

[0070] Concrete shrinkage test

[0071] According to T574-2020 "Cement Concrete Shrinkage Test Method", the concrete prepared in each embodiment and comparative example was subjected to early autogenous shrinkage test (age 5d) and drying shrinkage test (age 30d). The results are shown in Figure 3 .

[0072] Depend on Figure 3 It can be seen that the concrete of Examples 1-3 showed lower shrinkage in the early autogenous shrinkage test at the age of 5 days and the drying shrinkage test at the age of 30 days. This is because the multi-substance modified basalt fiber improves the internal structure of the concrete, and the graphene oxide and cement form a criss-cross network structure by overlapping and bridging each other, which improves the interfacial bonding strength between the basalt fiber and the cement-based matrix, improves the interfacial performance between the basalt fiber and the concrete, improves the bonding force between the concrete materials, and reduces the shrinkage of the concrete. After the grafted modified 4-sulfonic acid calixarene is combined with the basalt fiber, the complexing ability of the calixarene enables it to combine with metal ions to produce substances that block the pores of the concrete, reducing the water penetration channel, which also helps to reduce the shrinkage of the concrete.

[0073] Test Example 4

[0074] Concrete impermeability test

[0075] The water seepage height of the concrete prepared in each embodiment and comparative example was tested according to the water seepage height method in GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The chloride ion diffusion coefficient DRCM of each specimen was tested according to the RCM method in GB / T 0082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The results are shown in Table 1. Figure 4 .

[0076] Depend on Figure 4 It can be seen that the multi-substance modified basalt fiber improves the compactness of concrete. The synergistic effect of graphene oxide and basalt fiber and the improvement of the hydrophilicity of the basalt fiber surface by trisodium 1,6-diphosphate fructose make the concrete more compact and reduce the water penetration channels. The grafted modified 4-sulfonic acid calixarene combines with metal ions to produce substances that block the pores, further improving the impermeability of concrete. At the same time, calixarene reduces the agglomeration phenomenon between fibers, improves the dispersion of basalt fibers in the concrete matrix, and helps to enhance the impermeability of concrete.

[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0078] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A crack-resistant and anti-seepage concrete cement pole, characterized in that: It is composed of concrete and a steel skeleton buried in the concrete; the concrete includes the following components by weight: 300-350 parts of silicate cement, 100-120 parts of fine sand, 40-60 parts of fly ash, 100-150 parts of slag powder, 150-200 parts of coarse aggregate, 100-150 parts of water, 30-50 parts of multi-substance modified basalt fiber, 10-40 parts of carbon fiber, 10-40 parts of polypropylene fiber and 5-8 parts of water reducing agent; The multi-substance modified basalt fiber is prepared by the following steps: S1, dissolving 6,6'-iminodi-1-hexanol in dimethyl sulfoxide, then adding 4-sulfonic acid calixarene, heating to 70°C for reaction for 1.5h, then adding 4 mol / L sodium hydroxide solution to adjust the reaction solution to neutral, filtering, separating the liquids, and removing the solvent from the organic phase under reduced pressure to obtain grafted modified 4-sulfonic acid calixarene; S2, immersing the basalt fiber in a 4 mol / L sodium hydroxide solution, stirring at 100°C for 2 h, then filtering, washing and drying to obtain an alkali-etched basalt fiber, dispersing trisodium 1,6-diphosphate fructose and graphene oxide in ethanol, then adding the alkali-etched basalt fiber, soaking for 10 min for adsorption assembly, then taking out and drying to obtain a basalt fiber coated with the composite; S3, adding the composite-coated basalt fiber, grafted modified 4-sulfonic acid calixarene and silane coupling agent into deionized water, stirring at 80° C. for 3 h, then taking out and drying to obtain the multi-substance modified basalt fiber.

2. The anti-cracking and anti-seepage concrete cement pole according to claim 1, characterized in that: In the step S1, the weight ratio of 6,6'-iminodi-1-hexanol, dimethyl sulfoxide and 4-sulfonic acid calixarene is 1:55-75:0.3-0.

5.

3. The anti-cracking and anti-seepage concrete cement pole according to claim 2 is characterized in that: In the step S2, the weight ratio of trisodium fructose 1,6-diphosphate, graphene oxide, ethanol and alkali-etched basalt fiber is 3:2-5:300-500:10-20.

4. The anti-cracking and anti-seepage concrete cement pole according to claim 3 is characterized in that: In the step S3, the weight ratio of the composite-coated basalt fiber, the grafted modified 4-sulfonic acid calixarene, the silane coupling agent and the deionized water is 10:1-3:0.5-1:300-500.

5. The anti-cracking and anti-seepage concrete cement pole according to claim 4 is characterized in that: The silane coupling agent is one of KH550, KH560, KH570, KH602 and KH792.

6. The anti-cracking and anti-seepage concrete cement pole according to claim 5, characterized in that: The fine sand is river sand with a fineness modulus of 2.3-3.0 and a bulk density of 1500-1800 kg / m 3 .

7. The anti-cracking and anti-seepage concrete cement pole according to claim 6, characterized in that: The fly ash is S105 steel slag, with a particle size of less than 3mm and a bulk density of 2500-3000kg / m 3 .

8. The anti-cracking and anti-seepage concrete cement pole according to claim 7, characterized in that: The particle size of the coarse aggregate is 5-10 mm.

9. The anti-cracking and anti-seepage concrete cement pole according to claim 8, characterized in that: The water reducer is a combination of one or more of sodium lignin sulfonate, sodium gluconate, melamine and polycarboxylic acid water reducer.

10. A method for preparing the crack-resistant and anti-seepage concrete cement pole according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) After fine sand, coarse aggregate, multi-material modified basalt fiber, carbon fiber, and polypropylene fiber are mixed, silicate cement, fly ash, and slag powder are added for further mixing, and finally a water reducer and water are added to form concrete; (2) pouring concrete into a mold equipped with a steel mesh, centrifugally forming, curing for 18 hours, and obtaining the concrete cement pole after demoulding.

Citation Information

Patent Citations

  • Concrete containing basalt fiber as well as preparation method and application of concrete

    CN115368078A